Mega-lake formation in the eastern Hetao Basin, China, during marine isotope stages 7 and 5: A comparison of quartz and feldspar luminescence dating - Liu, JianGang; Fan, HaiYan; An, Ping; Wen, Huan; Yu, LuPeng (Frontiers in Earth Science, 2023)
Paleolacustrine sediments indicate a mega lake developed in the Hetao Basin (HTB), suggesting dramatic changes in the geomorphology and surface process of the Yellow River and surrounding regions. However, the formation time of the mega Hetao paleo-lake (HTPL) in HTB remains unclear. In this study, a set of 7.6-m-thick lacustrine sediment in the middle part of HTB is studied by both quartz optically stimulated luminescence (OSL) and K-feldspar (KF) post-infrared infrared stimulated luminescence (p-IR IRSL, pIRIR) dating. The results show that, 1) the quartz OSL ages do not increase with the depth as the KF pIRIR ages displayed, but saturated at ca. 80-100 ka with the consequence of age underestimation. The influence of signal saturation may occur below 96 Gy (ca. 32 ka) in this region. Thus, the KF pIRIR ages are chosen for geomorphologic evolution reconstruction. 2) These ages suggest the level of the HTPL exceeded 1033 m asl twice, i.e., at the early stages of MIS 7 (~255-245 ka) and MIS 5 (~130-120 ka). However, the exact scale of the HTPL and its relationship with the Jilantai Plaeolake is unclear. 3) This chronology suggests strong linkage between periodic formation of the HTPL and glacial-scale climatic change, and we propose an alternative hypothesis to interpret these processes, i.e., the Hobq Dunefield expanded eastward to dam the narrow Jin-Shaan Gorge during the glacial periods when the flows of the Yellow River was weak. Then in the beginning of the interglacial periods, the basin was filled by the abruptly resumed runoff in response to increased glacial meltwater and precipitation on the northeastern Tibetan Plateau. Once the lake spills out, the loose dune-dam may be breached quickly.